Hadith #5 - Sunan al-Nasa'i - Aisha bint Abi Bakr; Hameed bin Musa'da bin al-Mubarak حميد بن مسعدة بن المبارك; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Yazid bin Zari' يزيد بن زريع (Sunan al-Nasa'i)
“My father told me: ‘I heard ‘Aishah say, (narrating) from the Prophet (ﷺ): “Siwak is a means of purification for the mouth and is pleasing to the Lord.”
Grade:

Hadith #10 - Sunan al-Nasa'i - Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ma'mar bin Rashid معمر بن راشد; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي (Sunan al-Nasa'i)
“The Messenger of Allah (ﷺ) said: ‘The Fitrah are five: Trimming the mustache, plucking the armpit hairs, clipping the nails, removing the pubes, and circumcision.'”
Grade:

Hadith #112 - Sunan al-Nasa'i - Aisha bint Abi Bakr; Ash'uth bin Qays; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Masrouq bin al-Ajda' مسروق بن الأجدع; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“The Messenger of Allah (ﷺ) used to like to start with the right whenever he could, when purifying himself and when putting on shoes or combing his hair.” (One of the narrators) Shu’bah said: Then I heard Al-Ash’ath in Wasit, saying that he liked to start with the right, and he preferred that in all his affaris. Then I heard him in Al-Kufah saying that he liked to start with the right whenever he could.”
Grade:

Hadith #132 - Sunan al-Nasa'i - Amr bin 'Amir al-Bajli عمرو بن عامر البجلي الكوفي; Anas ibn Malik; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“The Messenger of Allah (ﷺ) was brought a small vessel (of water) and he performed Wudu’.” I said: “Did the Messenger of Allah (ﷺ) perform Wudu’ for every prayer?” He said: “Yes.” He said: “What about you?” He said: “We used to pray all the prayers so long as we did not commit Hadath.” He said: “And we used to pray all the prayers with (one) Wudu’.”
Grade:

Hadith #146 - Sunan al-Nasa'i - Hamran bin Aban حمران بن أبان; Jama' bin Shadad al-Maharbi جامع بن شداد المحاربي أبو صخرة; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Uthman ibn 'Affaan (Sunan al-Nasa'i)
“I heard Humran bin Aban tell Abu Burdah in the Masjid that he heard ‘Uthman narrating that the Messenger of Allah (ﷺ) said: ‘Whoever performs Wudu’ completely as commanded by Allah, the five daily prayers will be an expiation for whatever comes in between them.'”
Grade:

Hadith #158 - Sunan al-Nasa'i - al-Mandhir bin Ya'la al-Thauri منذر بن يعلى الثوري; Ali ibn Abi Talib; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Muhammad bin 'Ali b. al-Hussain al-Baqir محمد بن علي بن الحسين بن علي ,الباقر; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan al-Nasa'i)
“I felt too shy to ask the Messenger of Allah (ﷺ) about prostatic fluid because of Fatimah, so I told Al-Miqdad bin Al-Aswad to ask about it, and he (the Prophet (ﷺ)) said: ‘Perform Wudu’ for that.'”
Grade:

Hadith #159 - Sunan al-Nasa'i - Asim al-Ahwal عاصم الأحول; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Zar bin Habaysh bin Habasha زر بن حبيش بن حباشة (Sunan al-Nasa'i)
“I came to a man called Safwan bin ‘Assal and sat at his door. He came out and said: ‘What do you want?’ I said: ‘I am seeking knowledge.’ He said: ‘The angels lower their wings for the seeker of knowledge out of pleasure at what he is seeking.’ He said: ‘What do you want to know about?’ I said: ‘About the Khuffs.’ He said: ‘When we were with the Messenger of Allah (ﷺ) on a journey, he told us not to take them off for three days except in the case of Janabah, but not
Grade:

Hadith #184 - Sunan al-Nasa'i - Ibn Jurayj ابن جريج; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Muhammad bin Yusuf al-Baykandi محمد بن يوسف البيكندي البخاري; Sulayman ibn Yasar سليمان بن يسار مولى ميمونة بنت الحارث (Sunan al-Nasa'i)
“I entered upon Umm Salamah and she told me that the Messenger of Allah (ﷺ) used to wake up in a state of Janabah without having had a wet dream, then he would fast.” And she told him that she brought the Prophet (ﷺ) some grilled ribs and he ate from that, then he got up and prayed, and did not perform Wudu’.
Grade:

Hadith #185 - Sunan al-Nasa'i - ibn Abbas; Ibn Jurayj ابن جريج; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Muhammad bin Yusuf al-Baykandi محمد بن يوسف البيكندي البخاري (Sunan al-Nasa'i)
It was reported that Ibn ‘Abbas said “I witnessed (that) the Messenger of Allah (ﷺ) ate bread and meat, then stood for prayer and did not perform ablution. “
Grade:

Hadith #192 - Sunan al-Nasa'i - Abu Hurairah; Abu Rafi'; al-Hasan al-Basri الحسن البصري; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Qatada قتادة; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“When (a man) sits between the four parts of his wife’s body and exerts himself, then Ghusl becomes obligatory.”
Grade:

Hadith #229 - Sunan al-Nasa'i - Abdullah/Abu Bakr bin Hafs bin 'Umar عبد الله بن حفص بن عمر - أبو بكر; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“The Messenger of Allah (ﷺ) used to perform Ghusl from a vessel which was the size of a Faraq and he and I used to perform Ghusl using a single vessel.” Sixteen Ratls.
Grade:

Hadith #235 - Sunan al-Nasa'i - Abdur Rahman bin al-Qasim عبد الرحمن بن القاسم بن محمد بن أبي بكر; Aisha bint Abi Bakr; al-Qasim ibn Muhammad القاسم بن محمد بن أبي بكر الصديق; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“I remember competing over the vessel with the Messenger of Allah (ﷺ), when he and I were using it to perform Ghusl.”
Grade:

Hadith #307 - Sunan al-Nasa'i - Anas ibn Malik; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Qatada قتادة; Sa'id bin Abi Sa'id; Yazid bin Zari' يزيد بن زريع (Sunan al-Nasa'i)
“For Kufr.”
Grade:

Hadith #326 - Sunan al-Nasa'i - Makhariq bin Khalifa/'Abdullah مخارق بن خليفة; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Tarq bin 'Abdur Rahman طارق بن عبد الرحمن البجلي الأحمسي الكوفي; Umayya bin Khalid bin al-'Aswad أمية بن خالد بن الأسود (Sunan al-Nasa'i)
“Water is not made impure by anything.” See the following versions.
Grade:

Hadith #336 - Sunan al-Nasa'i - Abdullah bin Mughfal al-Mazni; Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Matruf bin Tarayf al-Harithi مطرف بن طريف; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Yazid bin Hameed, Abu Tiyah يزيد بن حميد أبو التياح الضبعي (Sunan al-Nasa'i)
“The Messenger of Allah (ﷺ) said: ‘If a dog licks the vessel of any one of you, let him throw (the contents) away and wash it seven times.'”
Grade:

Hadith #412 - Sunan al-Nasa'i - Abdur Rahman bin al-Qasim عبد الرحمن بن القاسم بن محمد بن أبي بكر; Aisha bint Abi Bakr; al-Qasim ibn Muhammad القاسم بن محمد بن أبي بكر الصديق; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
It was narrated from ‘Aishah that the Messenger of Allah (ﷺ) used to perform Ghusl, he and I from a single vessel, both of us scooping water from it.
Grade:

Hadith #426 - Sunan al-Nasa'i - Jabir ibn 'Abdullah; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“As for me, I pour water on my head three times.”
Grade:

Hadith #437 - Sunan al-Nasa'i - al-Mandhir bin Ya'la al-Thauri منذر بن يعلى الثوري; Ali ibn Abi Talib; Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Muhammad bin 'Ali b. al-Hussain al-Baqir محمد بن علي بن الحسين بن علي ,الباقر; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan al-Nasa'i)
“Ali, Al-Miqdad and ‘Ammar were talking. ‘Ali said: ‘I am a man who emits a lot of Madhi but I am too shy to ask the Messenger of Allah (ﷺ) about that because of his daughter’s position with me, so let one of you ask him.’ He told me that one of them – but I forgot who – asked him, and the Prophet (ﷺ) said: ‘That is Madhi. If any one of you notices that, let him wash it off himself and perform Wudu’ as for prayer or similar to the Wudu’ of prayer.'”
Grade:

Hadith #473 - Sunan al-Nasa'i - Ali ibn Abi Talib; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Qatada قتادة; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Ubaida bin 'Amr al-Salamani عبيدة بن عمرو (Sunan al-Nasa'i)
“I heard the Messenger of Allah (ﷺ) say: ‘He will never enter the Fire, the one who prays before the sun rises and before it sets.'”
Grade:

Hadith #481 - Sunan al-Nasa'i - Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Salmah bin Kahayl al-Hadrami سلمة بن كهيل بن حصين; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“I heard the Messenger of Allah (ﷺ) say: ‘Among the prayers is a prayer which, if a person misses it, it is as if he has robbed of his family and his wealth.” Ibn ‘Umar said: “I heard the Messenger of Allah (ﷺ) say: ‘It is ‘Asr prayer.'” Muhammad bin Ishaq contradicted him. That is, Muhammad bin Ishaq narrated it from Yazid bin Abi Habib with the following chain and wording, which differs with this narration, reported by Al-Laith from Yazid.
Grade:

Hadith #499 - Sunan al-Nasa'i - Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Siyar bin Salaama, Abu al-Minhal سيار بن سلامة الرياحي أبو المنهال (Sunan al-Nasa'i)
“We complained to the Messenger of Alalh (ﷺ) about how hot the sand was, but he did not respond to our complaint.” It was said to Abu Ishaq (one of the narrators): “Did they complain regarding his praying it early?” He said: “Yes.”
Grade:

Hadith #519 - Sunan al-Nasa'i - Abdullah bin Tawus عبد الله بن طاوس; Abu Hurairah; ibn Abbas; Ma'mar bin Rashid معمر بن راشد; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Tawus bin Kaysan طاوس (Sunan al-Nasa'i)
“Whoever catches up with a Rak’ah of the Subh prayer before the sun rises, then he has caught up with Subh, and whoever catches up with a Rak’ah of ‘Asr prayer before the sun sets, then he has caught up with ‘Asr.”
Grade:

Hadith #520 - Sunan al-Nasa'i - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ma'mar bin Rashid معمر بن راشد; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى (Sunan al-Nasa'i)
‘Are you not going to pray?’ He said: ‘The Messenger of Allah (ﷺ) said: ‘There is no prayer after ‘Asr until the sun has set, nor after Subh until the sun has risen.'”
Grade:

Hadith #557 - Sunan al-Nasa'i - Anas ibn Malik; Isma'il bin Mas'ud al-Jhdry إسماعيل بن مسعود الجحدري; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“Whoever catches up with a Rak’ah of the prayer, then he has caught up with the prayer.”
Grade:

Hadith #586 - Sunan al-Nasa'i - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ma'mar bin Rashid معمر بن راشد; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Umm Salamah; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
“I came to the Messenger of Allah, who became Muslim with you?’ He said: ‘Free men and slaves.’ I said: ‘Is there any moment which brings one closer to Allah than another?’ He said: ‘Yes, the last part of the night, so pray as much as you want until you pray Subh, then stop until the sun has risen until and it looks like a shield and (its shinning)spreads. Then pray as much as you want until an object’s shadow is at its shortest, then stop until the sun passes its zenith, for Hel
Grade:

Hadith #610 - Sunan al-Nasa'i - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; ibn Abbas; Ibn Jurayj ابن جريج; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Saleem bin Aswad, Abu al-Ash'atha سليم بن أسود أبو الشعثاء المحاربي (Sunan al-Nasa'i)
“I never saw the Messenger of Allah (ﷺ) combine any two prayers except in Al-Muzdalifah, and on that day he prayed Subh before its time.”
Grade:

Hadith #652 - Sunan al-Nasa'i - Abu Hurairah; Isma'il bin Mas'ud al-Jhdry إسماعيل بن مسعود الجحدري; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Yazid bin Zari' يزيد بن زريع (Sunan al-Nasa'i)
“The final words of the Adhan of Bilal were: ‘Allahu Akbar, Allahu Akbar, Allahu Akbar; La ilaha illallah (Allah is the Greatest, Allah is the Greatest, there is none worthy of worship except Allah.)'”
Grade:

Hadith #774 - Sunan al-Nasa'i - Hamam bin Munabbih همام بن منبه بن كامل; Ibrahim al-Nakha'i إبراهيم النخعي; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan al-Nasa'i)
It was narrated from Awn bin Abi Juhaifah, from his father that, the Messenger of Allah(ﷺ) went out in a red Hullah, and he set up a short spear (Anazah) and prayed facing toward it, while dogs, women and donkeys were passing beyond it.
Grade:

Hadith #859 - Sunan al-Nasa'i - Abdullah bin al-Samit عبد الله بن الصامت; Abu al-Aliyya al-Bara', Ziyad bin Feroz أبو العالية البراء زياد بن فيروز; Abu Dharr al-Ghaffari; Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Muhammad bin Ibrahim bin al-Harith محمد بن إبراهيم بن الحارث; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“What kept you from praying? Are you not a Muslim man?” He said: “Yes, but I had already prayed with my family.” The Messenger of Allah (ﷺ)said to him: “When you come you should pray with the people even if you have already prayed.”
Grade:

Hadith #880 - Sunan al-Nasa'i - Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Malik bin al-Hwyrth; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Nsr bin 'Asim al-Lythy نصر بن عاصم الليثي البصري; Qatada قتادة; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
that when the Messenger of Allah (ﷺ) started to pray, he would raise his hands in level with his shoulders, and when he bowed and when he raised his head from bowing, he would raise them likewise and say “Sami Allahu liman hamidah, Rabbana wa lakal-hamd (Allah hears those who praise Him, our Lord, to You be praise.” And he did not do that when he prostrated.
Grade:

Hadith #970 - Sunan al-Nasa'i - Abu Hurairah; Ata' bin Abi Rabah عطاء بن أبي رباح; Ibn Jurayj ابن جريج; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى (Sunan al-Nasa'i)
“I prayed Isha’ prayer- meaning Al-‘Atamah behind Abu Hurairah and he recited: ‘When the heaven is split asunder’ and prostrated during it. When he had finished praying, I said: ‘O Abu Hurairah, (this is) a prostration that we are not used to.’ He said: ‘Abu Al-Qasim (ﷺ) did this prostration and I was (praying) behind him, and I will continue to do this prostration until I meet Abu Al-Qasim.
Grade:

Hadith #990 - Sunan al-Nasa'i - Abdullah bin 'Ubaidullah b. Abi Mulayka عبد الله بن عبيد الله بن أبي مليكة; Ibn Jurayj ابن جريج; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Marwan bin al-Hakam bin Abi al-'As; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Urwa ibn al-Zubayr عروة بن الزبير; Zayd ibn Thabit (Sunan al-Nasa'i)
The Messenger of Allah (ﷺ) recited ‘Ha- Mim Ad-Dukhan’ in Maghrib.
Grade:

Hadith #1007 - Sunan al-Nasa'i - Abdullah bin al-Sa'ib; Ibn Jurayj ابن جريج; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Aabad bin Musa محمد بن عباد بن موسى; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى (Sunan al-Nasa'i)
“I heard Abu Wa’il say: “A man said in the presence of Abdullah: ‘I recited Al-Mufassal in one rak’ah.’ He said: ‘That is like reciting poetry. I know the similar surahs that the Messenger of Allah (ﷺ) used to recite together.’ And he mentioned twenty surahs from Al-Mufassal, two by two in each rak’ah.”
Grade:

Hadith #1048 - Sunan al-Nasa'i - Aisha bint Abi Bakr; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Matruf bin Tarayf al-Harithi مطرف بن طريف; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“I prayed with the Messenger of Allah (ﷺ), and he bowed and said when bowing: ‘Subhana Rabbial-azim (Glory be to my Lord Almighty).’ And when prostrating: ‘Subhana Rabbial-‘Ala (Glory be to my Lord Most High).'”
Grade:

Hadith #1054 - Sunan al-Nasa'i - Anas ibn Malik; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Qatada قتادة; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
When the Messenger of Allah (ﷺ) stood to offer a voluntary prayer, he would say when he bowed: “Allahumma laka rak’atu wa bika amantu wa laka aslamtu wa alayka tawwakaltu, anta Rabbi, khasha’a sam’i wa basri wa lahmi wa dammi wa mukhi wa ‘asabi Lillahi Rabbil-‘Alamin ( O Allah, to You I have bowed, in You I believe, to You I have submitted and in You I put my trust. You are my Lord. My hearing, my sight, my flesh, my blood, my brain and my sinews are humbled before Allah, the Lord
Grade:

Hadith #1145 - Sunan al-Nasa'i - Amr bin Murrah bin 'Abdullah عمرو بن مرة بن عبد الله بن طارق; Hudhayfah ibn al-Yaman; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Muhammad bin Maymun, Abu Hamza محمد بن ميمون المروزي أبو حمزة السكري; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
When the Prophet of Allah (ﷺ) started to pray, he raised his hands, and when he bowed, he did likewise, and when he raised his head from bowing he did likewise, and when he raised his head from prostration, he did likewise, meaning he raised his hands.
Grade:

Hadith #1175 - Sunan al-Nasa'i - Ayman bin Nabil أيمن بن نابل الحبشي; Jabir ibn 'Abdullah; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan al-Nasa'i)
They prayed with Abu Musa and he said: “The Messenger of Allah (ﷺ) said: ‘When you are sitting then let the first words that any of you says be: At-tahiyyatu lillahi was-salawatu wat-tayyibat, as-salamu ‘alaika ayyuhan-Nabiyyu wa rahmatAllahi wa baraktuhu. As-salamu ‘alaina wa ‘ala ‘ibad illahis-salihin, ashahdu an la illaha ill-Allah wa ashhadu anna Muhammadan ‘abduhu wa rasuluhu (Allah compliments, prayers and pure words are due to Allah. Peace be upon you, O Prophet, and the m
Grade:

Hadith #1338 - Sunan al-Nasa'i - Abdullah ibn al-Harith ibn Nawfal; Aisha bint Abi Bakr; Asim al-Ahwal عاصم الأحول; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Muhammad bin Ibrahim bin Sdran محمد بن إبراهيم بن صدران; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“The Messenger of Allah (ﷺ) commanded me to recite Al-Mu’awwidhat following every prayer.”
Grade:

Hadith #1366 - Sunan al-Nasa'i - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Isma'il bin Mas'ud al-Jhdry إسماعيل بن مسعود الجحدري; Jabir ibn 'Abdullah; Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Umar ibn al-Khattab; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
“We fasted Ramadan with the Messenger of Allah (ﷺ), and the Prophet (ﷺ) did not lead us in Qiyam until there were seven days left of the month, then he led us in Qiyam until one-third of the night had passed. Then, when there were six days left, he did not lead us in Qiyam. When there were five days left, he led us in praying Qiyam until half the night had passed. We said: ‘O Messenger of Allah (SA), why don’t you lead us in praying Qiyam for the rest of the night?’ He said: ‘If a
Grade:

Hadith #1436 - Sunan al-Nasa'i - Abdullah bin 'Awn bin Artaban عبد الله بن عون بن أرطبان الخزار; ibn Abbas; Ibn Sirin محمد بن سيرين الأنصاري; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى (Sunan al-Nasa'i)
The Messenger of Allah (ﷺ) said: “On Friday, there is an hour when, if a Muslim slave asks Allah for something at that time, He will give it to him.”
Grade:

Hadith #1464 - Sunan al-Nasa'i - Abu Bakra al-Thaqafi; al-Hasan al-Basri الحسن البصري; Amr bin 'Ali bin Bahr al-Bahli عمرو بن علي بن بحر الباهلي; Ash'ath bin Abi al-Ash'atha أشعث بن أبي الشعثاء; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى (Sunan al-Nasa'i)
“The Messenger of Allah (ﷺ) said: ‘The sun and moon are two signs of Allah (SWT), the Most High, and they do not become eclipsed for death or birth of anyone, rather Allah (SWT), the Mighty and Sublime, strikes fear into His slaves through them.'”
Grade:

Hadith #1517 - Sunan al-Nasa'i - Anas ibn Malik; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Thabit bin Aslam Albanani ثابت بن أسلم البناني; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم (Sunan al-Nasa'i)
He saw the Messenger of Allah (ﷺ), when he prayed for rain, turn to face the Qiblah, turning his cloak around and raising his hands.
Grade:

Hadith #1551 - Sunan al-Nasa'i - Abu Bakra al-Thaqafi; al-Hasan al-Basri الحسن البصري; Ash'ath bin Abi al-Ash'atha أشعث بن أبي الشعثاء; Isma'il bin Mas'ud al-Jhdry إسماعيل بن مسعود الجحدري; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى (Sunan al-Nasa'i)
“We were with the Messenger of Allah (ﷺ) and the Iqamah for prayer was said. The Messenger of Allah (ﷺ) stood up and one group stood behind him while another group faced the enemy. He led those who were behind him in prayer, bowing once and prostrating twice. Then they went and took the place of those who had been facing the enemy, and that group came and the Messenger of Allah (ﷺ) led them in prayer, bowing once and prostrating twice. Then the Messenger of Allah (ﷺ) said the taslim an
Grade:

Hadith #1622 - Sunan al-Nasa'i - Hudhayfah ibn al-Yaman; Husayn bin 'Abdur Rahman al-Salmi حصين بن عبد الرحمن السلمي; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shaqayq bin Salmah al-Asadi شقيق بن سلمة الأسدي أبو وائل الكوفي; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“I asked ‘Aishah with what did he- meaning the Prophet (ﷺ)- start Qiyam Al-Lail? She said: ‘You have asked me something which no one before you has asked. The Messenger of Allah (ﷺ) used to say the takbir ten times, the tahmid ten times, the tasbih ten times, and the tahlil ten times, and pray for forgiveness ten times, and say: Allahummaghfirli, wahdini, warzuqni wa ‘afini. A’udhu billahi min diqil-maqami yawmal-qiyamah (O Allah, forgive me, guide me, grant me provision and good h
Grade:

Hadith #1635 - Sunan al-Nasa'i - Anas ibn Malik; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Sulaiman bin Tarkhan al-Taymi سليمان بن طرخان التيمي (Sunan al-Nasa'i)
“The Messenger of Allah (ﷺ) said: ‘The most beloved of fasting to Allah is the fasting of Dawud, peace be upon him. He used to fast one day and not the next. And the most beloved of prayer to Allah (SWT) is the prayer of Dawud. He used to sleep half the night, spend one-third of the night in prayer and sleep for one-sixth of it.'”
Grade:

Hadith #1733 - Sunan al-Nasa'i - Abdur Rahman bin al-Qasim عبد الرحمن بن القاسم بن محمد بن أبي بكر; Dhar bin 'Abdullah al-Marhabi ذر بن عبد الله المرهبي; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Sa'id bin 'Abdur Rahman bin Abza سعيد بن عبد الرحمن بن أبزي; Salma ibn al-Akwa; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Zubayd bin al-Harith زبيد بن الحارث اليامي (Sunan al-Nasa'i)
Abu Musa was between Makkah and Al-Madinah. He prayed ‘Isha with two rak’ahs, then he stood and prayed one rak’ah of witr in which he recited one hundred verses from An-Nisa’. Then he said: “I tried my best to place my feet where the Messenger of Allah (ﷺ) placed his, and to recite what the Messenger of Allah (ﷺ) recited.”
Grade:

Hadith #1851 - Sunan al-Nasa'i - Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Matruf bin Tarayf al-Harithi مطرف بن طريف; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Qatada قتادة; Qays bin 'Asim bin Snan; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
the Prophet came to visit ‘Abdullah bin Thabit (when he was sick) and found him very close to death. He called out to him and he did not respond, so the Messenger of Allah said: “Truly, to Allah we belong and truly, to Him we shall return,” and said: “We wanted you to live but we were overtaken by the decree of Allah, O Abu Ar-Rabi.” The women screamed and wept, and Ibn “Atik started telling them to quiet. The Messenger of Allah said: “Leave them; when the inevitable comes, no one
Grade:

Hadith #1912 - Sunan al-Nasa'i - Ayana bin 'Abdur rahman bin Jushan عيينة بن عبد الرحمن بن جوشن; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى (Sunan al-Nasa'i)
a poor woman fell sick and the Messenger of Allah was informed of her sickness. The Messenger of Allah used to visit the poor when they were sick and ask about them. The Messnger of Allah said: “If she dies, then inform me.” Then her funeral took place at night and they did not like to wake the Messenger of Allah. When morning came, the Messenger of Allah was told what had happened to her. He said: “Did I not tell you to inform me?” They said: “O Messenger of Allah, we did not like to
Grade:

Hadith #1941 - Sunan al-Nasa'i - al-Hasan al-Basri الحسن البصري; Ash'ath bin Abi al-Ash'atha أشعث بن أبي الشعثاء; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘Do not verbally abuse the dead, for they have reached the consequences of what they did.”‘
Grade:

Hadith #1965 - Sunan al-Nasa'i - Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan al-Nasa'i)
a man was brought to the Prophet for him to offer the funeral prayer, and he said: “Pray for your companion, for he owes a debt.” Abu Qatadah said: ” I will pay it.” The Prophet said: “In full?” He said: “In full.” So he prayed for him
Grade:

Hadith #2035 - Sunan al-Nasa'i - al-Musayyib bin Hazn b. Abi Wahb; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ma'mar bin Rashid معمر بن راشد; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Muhammad bin Thwr al-Sn'any محمد بن ثور الصنعاني أبو عبد الله; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي (Sunan al-Nasa'i)
“We were with Fadalah bin ‘Ubaid in the land of the Romans, and a companion of ours died. Fadalah ordered that his grave be made level, then he said: ‘I heard the Messenger of Allah commanding that it be made level.”‘
Grade:

Hadith #2052 - Sunan al-Nasa'i - Abdullah bin Ysar عبد الله بن يسار; Jama' bin Shadad al-Maharbi جامع بن شداد المحاربي أبو صخرة; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“May Allah curse the Jews and Christians who took the graves of their prophets as Masjids.” (Sahih) Chpater 107. It Is Disliked to Walk Between Grave Wearing Sibtiyah Sandals
Grade:

Hadith #2142 - Sunan al-Nasa'i - ibn Umar; Jabla bin Sahaym جبلة بن سحيم; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘The month is like this and like this and like this.” (One of the narrators) Muhammad bin ‘Ubaid clapped his hands three time to demonstrate it, then he withheld his left thumb the third time. Yahya bin Saeed said to Ismail (One of the narrators): “Form his father?’ He said: “No.”
Grade:

Hadith #2158 - Sunan al-Nasa'i - Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Khaythama bin 'Abdur Rahman خيثمة بن عبد الرحمن بن أبي سبرة; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan al-Nasa'i)
“I had Sahur with Hudhaifah, then we went out to pray. When we came to the Masjid we prayed two Rakahs, then the Iqamah for prayer was said, and there was only a short time between them.” Abu Hurairah said : “The Messenger of Allah said: ‘Eat Sahur, for in Sahur there is blessing.”
Grade:

Hadith #2206 - Sunan al-Nasa'i - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Hisham bin 'Urwa هشام بن عروة; Khalid bin Mahran al-Hadha' خالد بن مهران الحذاء; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
“Whoever spends the night of Ramadan in prayer (Qiyam) out of faith and in the hope of reward, he will be forgiven his previous sins.” ‘
Grade:

Hadith #2335 - Sunan al-Nasa'i - al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Hafsa bint Umar; ibn Umar; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم (Sunan al-Nasa'i)
“The Messenger of Allah came one day and said: ‘Do you have any food?’ I said: ‘No.’ He came in to me on another occasion, and I said: ‘O Messenger of Allah, we have been given some Hais.’ He said: “Then I will break my fast today, although I had started my day fasting.”‘
Grade:

Hadith #2342 - Sunan al-Nasa'i - ibn Umar; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Nafie' نافع مولى ابن عمر; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم (Sunan al-Nasa'i)
“There is no fast for one who does not intend (to fast) before dawn.”
Grade:

Hadith #2395 - Sunan al-Nasa'i - Abdullah bin 'Amr bin al-'Aas; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Matruf bin Tarayf al-Harithi مطرف بن طريف; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Sulaiman bin Tarkhan al-Taymi سليمان بن طرخان التيمي (Sunan al-Nasa'i)
“My father got me married to a woman and he came to visit her and said: ‘What do you think of your husband?’ She said: ‘What a wonderful man he is. He does not sleep at night and he does not break his fast during the day.’ He got upset with me and said: ‘I got you married to a woman from among the Muslims and you have neglected her.’ I did not pay attention to what he said because of my energy and love of worship. News of that reached the Prophet and he said: ‘But I stand (in pra
Grade:

Hadith #2399 - Sunan al-Nasa'i - Abdullah bin 'Amr bin al-'Aas; Habib bin Abi Thabit حبيب بن أبي ثابت قيس; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“Fast one day, and you will have the reward of what is left.” He said: “I am able to do more than that.” He (ﷺ) said: “Fast two days, and you will have the reward of what is left.” He said: “I am able to do more than that.” He (ﷺ) said: “Fast three days and you will have the reward of what is left.” He said: “I am able to do more than that.” He (ﷺ) said: “Fast four days and you will have the reward of what is left.” He said: “I am able to do more than that.”
Grade:

Hadith #2430 - Sunan al-Nasa'i - Anas bin Sirin أنس بن سيرين الأنصاري; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“You should fast the thirteenth, fourteenth and fifteenth.” (Hasan) Abu ‘Abdur-Rahman (An-Nasai) said: This is a mistake, it is not a narration of Bayan; perhaps Sufyan said: “It was narrated to us by two (Ithnan)” and the ‘Alif was dropped so it became Bayan.
Grade:

Hadith #2436 - Sunan al-Nasa'i - Bahz bin Hakim bin Mu'awiya al-Qushayri بهز بن حكيم بن معاوية; Hakeem bin Mu'awiyya bin Hayda حكيم بن معاوية بن حيدة القشيري; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى (Sunan al-Nasa'i)
the Prophet commanded them to fast the three days of Al-Bid. He said: “That is (equivalent to) fasting for the whole month.”
Grade:

Hadith #2449 - Sunan al-Nasa'i - Bahz bin Hakim bin Mu'awiya al-Qushayri بهز بن حكيم بن معاوية; Hakeem bin Mu'awiyya bin Hayda حكيم بن معاوية بن حيدة القشيري; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى (Sunan al-Nasa'i)
“My father told, me that my grandfather said: ‘I heard the Prophet say: With regard to grazing camels, for every forty a Bint Labbun (a two-year old female camel). No differentiation is to be made between camels when calculating them. Whoever gives it seeking reward, he will be rewarded for it. Whoever refuses, we will take it, and half of his camels, as one of the rights of our Lord. And it is not permissible for the family of Muhammad to have any of them.”‘
Grade:

Hadith #2480 - Sunan al-Nasa'i - al-Husain bin Dhakwan al-Mua'lam الحسين بن ذكوان المعلم المكتب; Amr bin Shu'aib bin Muhammad عمرو بن شعيب بن محمد السهمي; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى (Sunan al-Nasa'i)
“No Sadaqah is due on less than five Awsaq of dates, no Sadaqah is due on less than five Awaq of silver, and no Sadagah is due on less than five Dhawd (head) of camels.”
Grade:

Hadith #2538 - Sunan al-Nasa'i - Abu Musa al-Asha'ari; Bryd bin 'Abdullah بريد بن عبد الله بن أبي; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
the Messenger of Allah said, when mentioning charity and those who refrain from asking. “The upper hand is better than the lower hand; the upper hand is that which gives and the lower hand is that which asks.”
Grade:

Hadith #2555 - Sunan al-Nasa'i - Harithh bin Wahb al-Khza'y; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Ma'bad bin Khalid al-Jadli معبد بن خالد الجدلي; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“Do not count what you give, otherwise Allah, the Mighty and Sublime, will count what He gives to you.”
Grade:

Hadith #2566 - Sunan al-Nasa'i - Bahz bin Hakim bin Mu'awiya al-Qushayri بهز بن حكيم بن معاوية; Hakeem bin Mu'awiyya bin Hayda حكيم بن معاوية بن حيدة القشيري; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى (Sunan al-Nasa'i)
“The one who recites the Qur’an loudly is like one who gives charity openly, and the one who recites the Qur’an quietly is like one who gives charity in secret.”
Grade:

Hadith #2568 - Sunan al-Nasa'i - Bahz bin Hakim bin Mu'awiya al-Qushayri بهز بن حكيم بن معاوية; Hakeem bin Mu'awiyya bin Hayda حكيم بن معاوية بن حيدة القشيري; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى (Sunan al-Nasa'i)
“There are three to whom Allah will not speak on the Day of Resurrection, or look at them, or sanctify them, and theirs will be a painful torment.” The Messenger of Allah repeated and Abu Dharr said: “May they be lost and doomed.” He said: “The one who lets his garment hang beneath his ankles, a vendor who tries to sell his product by means of false oaths, and the one who reminds people of what he has given them.”
Grade:

Hadith #2582 - Sunan al-Nasa'i - Abdullah bin 'Awn bin Artaban عبد الله بن عون بن أرطبان الخزار; Hafsa bint Umar; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى (Sunan al-Nasa'i)
“The Messenger of Allah said: “The one who strives to sponsor a widow or a poor person is like the one who strives in Jihad in the cause of Allah, the Mighty and Sublime.”‘
Grade:

Hadith #2621 - Sunan al-Nasa'i - al-Nu'man bin Salm al-Ta'ify النعمان بن سالم الطائفي; Amr bin Aws bin Abi Aws عمرو بن أوس بن أبي أوس; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Mas'ud bin Malik Abu Razayn al-Asadi مسعود بن مالك أبو رزين الأسدي; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
he gave someone a horse to ride in the cause of Allah, then he saw it offered for sale and wanted to buy it. The Prophet said to him: “Do not think of buying back what you have given in charity.”
Grade:

Hadith #2742 - Sunan al-Nasa'i - Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Qays bin Muslim al-Jadli قيس بن مسلم الجدلي; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Tariq bin Shahab (Sunan al-Nasa'i)
“Mu’awiyah saide to Ibmn ‘Abbas: “do you know that I cut the hair of the Messenger of Allah at Al-Marwah?” He said: “No.” Ibn ‘Abbas said: “This Mu’awiyah forbids the people to perform Tamattu’ but the Prophet performed Tamattue.”
Grade:

Hadith #2771 - Sunan al-Nasa'i - al-Miswar bin Makhrama bin Nawfal; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ma'mar bin Rashid معمر بن راشد; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Muhammad bin Thwr al-Sn'any محمد بن ثور الصنعاني أبو عبد الله; Urwa ibn al-Zubayr عروة بن الزبير (Sunan al-Nasa'i)
“I asked Sa’eed bin Jubair about a man who performs Hajj and stipulates a condition. He said: ‘Conditions are something that people do among themselves.’ I narrated the Hadith of ‘Ikrimah to him, and he narrated to me from Ibn ‘Abbas, that Duba’ah bint Az-Zubair bin ‘Abdul-Muttalib came to the Prophet, and said: ‘O Messenger of Allah, I want to perform Hajj, so what should I say?’ He said: ‘Say: Labbaik Allahumma! Labbaika wa mahilli min al-ardihayth tahbisuni (Here I am,
Grade:

Hadith #2824 - Sunan al-Nasa'i - Abdullah bin Abi Qatada Ibn Rab'i عبد الله بن أبي قتادة الأنصاري السلمي; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
he gave the Messenger of Allah an onager when he was in Al-Abwa or in Waddan, but the Messenger of Allah gave it back to him. “And when the Messenger of Allah saw the expression on my face he said: “We only gave it back to you because we are in Ihram.'”
Grade:

Hadith #2854 - Sunan al-Nasa'i - ibn Abbas; Ja'far bin Iyas; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Sa'id bin Jubayr سعيد بن جبير الأسدي; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
That the Prophet was treated by means of cupping when he was in Ihram for a contusion that he had suffered. (Diaf)
Grade:

Hadith #2902 - Sunan al-Nasa'i - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Aisha bint Abi Bakr; al-Aswad bin Yazid الأسود بن يزيد بن قيس النخعي; Isma'il bin Mas'ud al-Jhdry إسماعيل بن مسعود الجحدري; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
when the Prophet came to a place in Dar Yala he turned to face the Qiblah and supplicated. (Daif)
Grade:

Hadith #2905 - Sunan al-Nasa'i - Abdullah bin 'Awn bin Artaban عبد الله بن عون بن أرطبان الخزار; ibn Umar; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Nafie' نافع مولى ابن عمر (Sunan al-Nasa'i)
“One prayer in this Masjid of mine is better than a thousand prayers in any other Masjid except Al-Masjid Al-Kabah.'”
Grade:

Hadith #2921 - Sunan al-Nasa'i - ibn Abbas; Ibn Jurayj ابن جريج; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Sulaiman bin Abi Muslim al-Ahwal سليمان بن أبي مسلم سليمان الأحول; Tawus bin Kaysan طاوس (Sunan al-Nasa'i)
“I entered the House with the Messenger of Allah. He sat and praised Allah, and recited the Takbir, and the Tahlil. Then he went to the wall of the House that was in front of him, and placed his chest, cheek and hands on it, then he recited the Takbir, and the Tahlil, and supplicated. And he did that in all the corners, then he came out, and turned to face the Qiblah while he was in front of the door, and he said: ‘This is the Qiblah, this is the Qiblah.'”
Grade:

Hadith #3078 - Sunan al-Nasa'i - ibn Abbas; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Lahaaq bin Hameed bin Sa'id لاحق بن حميد بن سعيد أبو مجلز; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Qatada قتادة; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“I sqa Ibn Masud stone Jamratul ‘Aqabah from the bottom of the valley, then he said: ;This – by the One beside Whom there is no other God-is the place where the one to whom Surat Al-Baqarah was revealed stood.”‘
Grade:

Hadith #3087 - Sunan al-Nasa'i - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Hurairah; Ahmed bin 'Amr bin al-Sarh أحمد بن عمرو بن السرح أبو الطاهر; al-Harith bin Mskyn bin Muhammad الحارث بن مسكين بن محمد; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ma'mar bin Rashid معمر بن راشد; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Sa'id bin Abi Sa'id; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan al-Nasa'i)
Al-Fadl to him that he roed behind the Messenger of Allah and he continued to recited the Talbiyah until eh stoned the Jamrat.
Grade:

Hadith #3137 - Sunan al-Nasa'i - Ibn Jurayj ابن جريج; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Sulayman ibn Yasar سليمان بن يسار مولى ميمونة بنت الحارث; Yonus bin Yusuf bin Hmas يونس بن يوسف بن حماس (Sunan al-Nasa'i)
“O Abu Sa’eed! Whoever is content with Allah as Lord, Islam as his religion and Muhammad as Prophet, then he is guaranteed Paradise.” Abu Sa’eed found this amazing and said: “Say it to me again, O Messenger of Allah.” So he did that, then the Messenger of Allah (ﷺ) said: “And there is something else by means of which a person may be raised one hundred degrees in Paradise, each of which is like that which is between the Heaven and the Earth.” He said: “What is it, O Messenger
Grade:

Hadith #3143 - Sunan al-Nasa'i - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Ma'dan bin Abi Talha معدان بن أبي طلحة ويقال بن طلحة; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Qatada قتادة; Salm bin Abi al-Ja'd سالم بن أبي الجعد (Sunan al-Nasa'i)
“O Shaikh, tell me of a Hadith that you heard from the Messenger of Allah (ﷺ).” (He said: “Yes; I heard the Messenger of Allah (ﷺ)) say: ‘The first of people for whom judgment will be passed on the Day of Resurrection are three. A man who was martyred. He will be brought and Allah will remind him of His blessings and he will acknowledge them. He will say: What did you do with them? He will say: I fought for Your sake until I was martyred. He will say: You are lying. You fought so tha
Grade:

Hadith #3145 - Sunan al-Nasa'i - Amr bin 'Absa al-Salmi; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Sharhbayl bin al-Samat (Sunan al-Nasa'i)
“Whoever fights seeking only an ‘Iqbal, then he will have what he intended.”
Grade:

Hadith #3267 - Sunan al-Nasa'i - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
“A previously married woman has more right to decide about herself (with regard to marriage) than her guardian, and an orphan girl should be consulted, and her permission is her silence.”
Grade:

Hadith #3297 - Sunan al-Nasa'i - Asim al-Ahwal عاصم الأحول; Jabir ibn 'Abdullah; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
a woman and her paternal aunt or a woman and her maternal aunt.
Grade:

Hadith #3333 - Sunan al-Nasa'i - Abu 'Alqama أبو علقمة; Abu Sa'id al-Khudri; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Qatada قتادة; Sa'id bin Abi Sa'id; Salah bin Abi Maryam صالح بن أبي مريم الضبعي - أبو الخليل; Yazid bin Zari' يزيد بن زريع (Sunan al-Nasa'i)
“Why do you do that?” We said: “A man may have a wife, and he has intercourse with her, but he does not want her to get pregnant, or he may have a concubine, and he has intercourse with her, but he does not want her to get pregnant.” He said: “It does not make any difference if you do that, for it is the matter of Al-Qadr.”
Grade:

Hadith #3370 - Sunan al-Nasa'i - Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Muhammad bin Hatib bin al-Harith; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“If he forced her, then she is free at his expense and he has to give her mistress a similar slave as a replacement. If she obeyed him in that, then she belongs to her mistress, and he has to give her mistress a similar slave as well.”
Grade:

Hadith #3371 - Sunan al-Nasa'i - al-Hasan al-Basri الحسن البصري; Amr bin 'Ali bin Bahr al-Bahli عمرو بن علي بن بحر الباهلي; Ash'ath bin Abi al-Ash'atha أشعث بن أبي الشعثاء; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى (Sunan al-Nasa'i)
“You are confused, the Messenger of Allah forbade it, and the meat of domestic donkeys on the day of Khaibar.”
Grade:

Hadith #3396 - Sunan al-Nasa'i - ibn Umar; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Nafie' نافع مولى ابن عمر; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم (Sunan al-Nasa'i)
“Tell him to take her back and keep her until she becomes pure, then menstruates again and becomes pure again. Then if he wishes he may keep her, or if he wishes, he may divorce her before he touches (has intercourse with) her. This is the time when Allah, the Mighty and Sublime, has stated that women may be divorced.”
Grade:

Hadith #3426 - Sunan al-Nasa'i - Abdur Rahman bin Ka'b bin Malik; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ka'b bin Malik bin Abi Ka'b; Ma'mar bin Rashid معمر بن راشد; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Muhammad bin Thwr al-Sn'any محمد بن ثور الصنعاني أبو عبد الله (Sunan al-Nasa'i)
“A man came to him and said: ‘I have made my wife forbidden to myself.’ He said: ‘You are lying, she is not forbidden to you.’ Then he recited this Verse: ‘O Prophet! Why do you forbid (for yourself) that which Allah has allowed to you.’ (And he said): ‘You have to offer the severest form of expiation: Freeing a slave.'”
Grade:

Hadith #3440 - Sunan al-Nasa'i - Aisha bint Abi Bakr; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ma'mar bin Rashid معمر بن راشد; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Muhammad bin Thwr al-Sn'any محمد بن ثور الصنعاني أبو عبد الله; Urwa ibn al-Zubayr عروة بن الزبير (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘Allah, the Mighty and Sublime, has forgiven my Ummah for what is whispered to them or what enters their minds, so long as they do not act upon it or speak of it.'”
Grade:

Hadith #3442 - Sunan al-Nasa'i - Aisha bint Abi Bakr; Amir al-Sha'bi عامر الشعبي; Asim al-Ahwal عاصم الأحول; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Masrouq bin al-Ajda' مسروق بن الأجدع; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“The Messenger of Allah had a Persian neighbor who was good at making soup. He came to the Messenger of Allah one day when ‘Aishah was with him, and gestured to him with his hand to come. The Messenger of Allah gestured toward ‘Aishah -meaning: ‘What about her?’- and the man gestured to him like this, meaning, ‘No,’ two or three times.”
Grade:

Hadith #3444 - Sunan al-Nasa'i - Aisha bint Abi Bakr; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Masrouq bin al-Ajda' مسروق بن الأجدع; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Muslim bin Sabih al-Hamdani, Abu al-Daha مسلم بن صبيح أبو الضحى; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan al-Nasa'i)
“Look at how Allah diverts the insults and curses of Quraish from me. They insult ‘Mudhammam’ and curse ‘Mudhammam’ -but I am Muhammad.”
Grade:

Hadith #3459 - Sunan al-Nasa'i - al-Hakam bin Aban الحكم بن أبان العدني; Ikrama عكرمة; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى (Sunan al-Nasa'i)
“Al-Wala’ is to the one who did the favor (of setting the slave free).” The Messenger of Allah gave her the choice, as her husband was a slave. And she gave some meat to ‘Aishah as a gift, and the Messenger of Allah said: “Why don’t you give me some of this meat?” ‘Aishah said: “It was given in charity to Barirah.” He said: “It is a charity for her, and a gift for us.”
Grade:

Hadith #3496 - Sunan al-Nasa'i - Hilal bin Abi Maymuna هلال بن علي بن أسامة; Ibn Jurayj ابن جريج; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Ziyad bin 'Alaqa زياد بن علاقة (Sunan al-Nasa'i)
“I was with the Messenger of Allah, and ‘Ali, may Allah be pleased with him, was in Yemen at that time. A man came to him and said: ‘I saw ‘Ali when three men were brought to him who all claimed (to be the father) of a child. ‘Ali said to one of them: Will you give the child up to him? And he refused. He said to (the next one): Will you give the child up to him? And he refused. He said to (the next one): Will you give the child up to him? And he refused. ‘Ali said: You are disputing
Grade:

Hadith #3501 - Sunan al-Nasa'i - Hameed bin Nafi' al-Ansari حميد بن نافع الأنصاري; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Umm Salamah; Zaynab bint Abi Salamah (Sunan al-Nasa'i)
“O Allah, guide him,” and (the child) went to his father.
Grade:

Hadith #3521 - Sunan al-Nasa'i - Abdullah bin 'Awn bin Artaban عبد الله بن عون بن أرطبان الخزار; Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; Ibn Sirin محمد بن سيرين الأنصاري; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى (Sunan al-Nasa'i)
“Ibn ‘Abbas, Abu Hurairah and I were together, and Ibn ‘Abbas said: ‘If a woman gives birth after her husband dies, her ‘Iddah is the longer of the two periods.'” Abu Salamah said: “We sent Kuraib to Umm Salamah to ask her about that. He came to us and told us from her that the husband of Subai’ah died and she gave birth a few days after her husband died, and the Messenger of Allah told her to get married.”
Grade:

Hadith #3570 - Sunan al-Nasa'i - Ibn Jurayj ابن جريج; Jabir ibn 'Abdullah; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘There is goodness tied to the forelocks of horses until the Day of Resurrection. And horses are of three types: Those that bring reward to man, those that are a means of protection for a man, and those that are a burden (of sin) for a man. As for those that bring reward, they are kept for the cause of Allah and for Jihad. No fodder enters their stomach but for everything that enters their stomachs, reward is written for him, even if he puts them out to pasture.
Grade:

Hadith #3720 - Sunan al-Nasa'i - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Tawus bin Kaysan طاوس; Zayd ibn Thabit (Sunan al-Nasa'i)
“Ruqba and ‘Umra are not permissible; whoever is given something on the basis of ‘Umra, it is his, and whoever is given something on the basis of Ruqba, it is his.”
Grade:

Hadith #3737 - Sunan al-Nasa'i - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Jabir ibn 'Abdullah; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan al-Nasa'i)
“The Messenger of Allah forbade ‘Umra and Ruqba.” I said: “What is Ruqba?” He said: “When one man says to another: ‘This belongs to you for the rest of your life.’ But if you do that, it is permissible.”
Grade:

Hadith #3738 - Sunan al-Nasa'i - Da'ud bin Abi Hnd داود بن أبي هند; Jabir ibn 'Abdullah; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan al-Nasa'i)
“I heard Qatadah narrating from ‘Ata’, from Jabir that the Prophet said: ‘Umra is permissible.'”
Grade:

Hadith #3750 - Sunan al-Nasa'i - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Jabir ibn 'Abdullah; Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘Umra (a lifelong gift) belongs to the one to whom it was given; it belongs to him and to his heirs, and is inherited by those among his descendants who inherit from him.'”
Grade:

Hadith #3782 - Sunan al-Nasa'i - Abdur Rahman bin Samra; al-Hasan al-Basri الحسن البصري; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Sulaiman bin Tarkhan al-Taymi سليمان بن طرخان التيمي (Sunan al-Nasa'i)
“You are setting up rivals (to Allah) and associating others (with Him). You say: ‘Whatever Allah wills and you will,’ and you say: ‘By the Ka’bah.'” So the Prophet commanded them, if they wanted to swear an oath, to say: “By the Lord of the Ka’bah;” and to say: “Whatever Allah wills, then what you will.”
Grade:

Hadith #3809 - Sunan al-Nasa'i - Imran bin Husain; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Nasr bin 'Imran bin Isam نصر بن عمران بن عصام; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Zahdam bin Madrab, Abu Muslim زهدم بن مضرب أبو مسلم الجرمي (Sunan al-Nasa'i)
“In Al-Madinah we used to buy and sell Wasqs (of goods), and we used to call ourselves Samasir (brokers), and the people used to call us like that. The Messenger of Allah came out to us one day, and called us by a name that was better than that which we called ourselves and which the people called us. He said: ‘O Tujjar (traders), your selling involves (false) oaths and lies, so mix some charity with it.'”
Grade:

Hadith #3810 - Sunan al-Nasa'i - ibn Abbas; Ibn Jurayj ابن جريج; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Sulaiman bin Abi Muslim al-Ahwal سليمان بن أبي مسلم سليمان الأحول; Tawus bin Kaysan طاوس (Sunan al-Nasa'i)
“They do not bring any good; they are just a means of taking wealth from the miserly.”
Grade:

Hadith #3933 - Sunan al-Nasa'i - Abdul al-Kareem bin Malik عبد الكريم بن مالك الجزري أبو سعيد; ibn Abbas; Ma'mar bin Rashid معمر بن راشد; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Sa'id bin Jubayr سعيد بن جبير الأسدي (Sunan al-Nasa'i)
“Zuhair bin Rafi’ came to us and said: ‘The Messenger of Allah forbade me to do something that was convenient for us.’ I said: ‘What was that?’ He said: ‘The command of the Messenger of Allah is true. He asked me: What do you do with your land? I said: We rent it out in return for one-quarter (of the yield) and a number of Wasqs of dates or barley. He said: Do not do that. Cultivate it, give it to someone else to cultivate, or keep it.'”
Grade:

Hadith #3992 - Sunan al-Nasa'i - ibn Mas'ud; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shaqayq bin Salmah al-Asadi شقيق بن سلمة الأسدي أبو وائل الكوفي; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan al-Nasa'i)
“I heard Aws say: ‘I came to the Messenger of Allah said: Leave him alone. Then he said: I have been commanded to fight the people until they say La ilaha illallah. If they say it, then their blood and their wealth become forbidden to me, except for a right that is due. (One of the narrators) Muhammad said: I said to Shu’bah: ‘Doesn’t the Hadith contain: Does he not testify to La ilaha illallah (there is none worthy of worship except Allah) and that I am the Messenger of Allah?’ He
Grade:

Hadith #4010 - Sunan al-Nasa'i - Anas ibn Malik; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Ubaidullah bin Abi Bakr عبيد الله بن أبي بكر بن أنس (Sunan al-Nasa'i)
“The people of Al-Kufah differed concerning this Verse: “And whoever kills a believer intentionally.” So I went to Ibn ‘Abbas and asked him, and he said: ‘It was revealed among the last of what was revealed, and nothing of it was abrogated after that.'”
Grade:

Hadith #4032 - Sunan al-Nasa'i - Anas ibn Malik; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Qatada قتادة; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Yazid bin Zari' يزيد بن زريع (Sunan al-Nasa'i)
“I heard the Messenger of Allah ) when they are all united, strike him with the sword.'”
Grade:

Hadith #4084 - Sunan al-Nasa'i - Abdullah bin 'Amr bin al-'Aas; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Hatm bin Isma'il al-Madni حاتم بن إسماعيل المدني; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى (Sunan al-Nasa'i)
“Abu Bakr became infuriated with a man.” He said: “If you tell me to, I will do it.” He said: “By Allah, that is not for any human being after Muhammad .”
Grade:

Hadith #4192 - Sunan al-Nasa'i - Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“Among the delegation of Thaqif there was a man who suffered from leprosy. The Prophet sent word to him saying: ‘Go back, for I have accepted your pledge.”‘
Grade:

Hadith #4220 - Sunan al-Nasa'i - al-Hasan al-Basri الحسن البصري; Amr bin 'Ali bin Bahr al-Bahli عمرو بن علي بن بحر الباهلي; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Qatada قتادة; Sa'id bin Abi Sa'id; Samra bin Jundub; Yazid bin Zari' يزيد بن زريع (Sunan al-Nasa'i)
“We were with the Prophet in a gathering and he said: ‘Pledge to me that you will not associate anything with Allah, you will not steal, and you will not have unlawful sexual relations.’ He recited the Verse to them (and said) Whoever does any of these things, and Allah conceals him then it is up to Allah, the mighty and Sublime: If He wills, He will punish him, and if He wills, He will forgive him.
Grade:

Hadith #4301 - Sunan al-Nasa'i - Adi ibn Hatim al-Tayyi'; Isma'il bin Mas'ud al-Jhdry إسماعيل بن مسعود الجحدري; Ja'far bin Iyas; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Sa'id bin Jubayr سعيد بن جبير الأسدي; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“The Messenger of Allah said: “Whoever keeps a dog, except a dog for herding livestock or a dog for hunting, one Qirat will be deducted from his reward each day.” ‘Abdullah said: “Abu Hurairah said: ‘Or a dog for farming.'”
Grade:

Hadith #4302 - Sunan al-Nasa'i - Abdul Malik bin Mysrh عبد الملك بن ميسرة الزراد; Adi ibn Hatim al-Tayyi'; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Sa'id bin Jubayr سعيد بن جبير الأسدي; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“The Messenger of Allah forbade the price of a dog, the gift of a female fornicator and the fees of a fortuneteller.”( Sahih)
Grade:

Hadith #4304 - Sunan al-Nasa'i - Adi ibn Hatim al-Tayyi'; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Mry bin Qtry al-Kwfy مري بن قطري; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Smak bin Hrb bin Aws سماك بن حرب بن أوس (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘The worst of earnings arte the gift of a female fornicator, the price of a dog and the earnings of a cupper.””
Grade:

Hadith #4338 - Sunan al-Nasa'i - Abdur-Razzaq عبد الرزاق بن همام; al-Bara' bin Azib bin al-Harith; Amir al-Sha'bi عامر الشعبي; Asim al-Ahwal عاصم الأحول; Ma'mar bin Rashid معمر بن راشد; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى (Sunan al-Nasa'i)
“The Messenger of Allah allowed us to eat the flesh of horses but he forbade the flesh of donkeys.”
Grade:

Hadith #4376 - Sunan al-Nasa'i - Ali ibn Abi Talib; Hjyh bin Ady al-Kndy al-Kwfy حجية بن عدي; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Salmah bin Kahayl al-Hadrami سلمة بن كهيل بن حصين; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
‘Abdullah told him that the Messenger of Allah used to offer the sacrifice at the prayer place.
Grade:

Hadith #4384 - Sunan al-Nasa'i - Asim bin Kulayb bin Shahab عاصم بن كليب بن شهاب بن المجنون; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Kulayb bin Shahab كليب بن شهاب; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“The Messenger of Allah forbade sacrificing an animals with its ears slit form the front, and animals with its ears slit form the back, and animal with its ears slit lengthwise, an animals with a round hole in tits ear, or an animals with its nose cut off”
Grade:

Hadith #4401 - Sunan al-Nasa'i - Adi ibn Hatim al-Tayyi'; Isma'il bin Mas'ud al-Jhdry إسماعيل بن مسعود الجحدري; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Mry bin Qtry al-Kwfy مري بن قطري; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Smak bin Hrb bin Aws سماك بن حرب بن أوس (Sunan al-Nasa'i)
“When distributing the spoils of war, the Messenger of Allah used to make ten sheep equivalent to one camel.” Shu’bah said: “I know most if it from what I heard form Sa’eed bin Masruq, and Sufyan narrated it to me.” (Sahih )
Grade:

Hadith #4418 - Sunan al-Nasa'i - Anas ibn Malik; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Qatada قتادة; Sa'id bin Abi Sa'id; Yazid bin Zari' يزيد بن زريع (Sunan al-Nasa'i)
“I said: “O Messenger of Allah, is slaughtering only in the throat or upper chest?” He said: ‘If you stab it in the thigh, that will suffice,”‘(Daif)
Grade:

Hadith #4494 - Sunan al-Nasa'i - Abdullah bin 'Awn bin Artaban عبد الله بن عون بن أرطبان الخزار; Anas ibn Malik; Ibn Sirin محمد بن سيرين الأنصاري; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى (Sunan al-Nasa'i)
a man told the Messenger of Allah that he was always being cheated. The Messenger of Allah said to him: “When you make a deal, say: There is no intention of cheating” So, whenever the man engages in a deal he says, ‘There is no intention of cheating.” “(Sahih )
Grade:

Hadith #4507 - Sunan al-Nasa'i - Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ma'mar bin Rashid معمر بن راشد; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Yazid bin Zari' يزيد بن زريع (Sunan al-Nasa'i)
the Messenger of Allah forbade artificially inflating prices, meeting traders on the way, and for a town-dweller to sell for a desert-dweller.” (Sahih )
Grade:

Hadith #4517 - Sunan al-Nasa'i - Abu Hurairah; Hafs bin 'Asim bin 'Umar حفص بن عاصم بن عمر; Khbyb bin 'Abdur Rahman خبيب بن عبد الرحمن بن خبيب; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم (Sunan al-Nasa'i)
“No tow-dweller should sell for desert-dweller, no man should outbid his brother; and no woman should ask for her sister (in faith) to be divorced so as to turn over what is in her bowl (deprive her of her share of maintenance)”
Grade:

Hadith #4525 - Sunan al-Nasa'i - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Jabir ibn 'Abdullah; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan al-Nasa'i)
“The Messenger of Allah forbade two kinds of garments and two kinds of transactions. As for the two kinds of transactions, they are Mulamash and Munabadhaha. Munabadha is when a man says, ‘I throw this garment, and the transaction becomes binding, and Mulamasah is when a man touches it with his had, without spreading it out and checking it, and once he touches it, the transaction becomes binding.”
Grade:

Hadith #4590 - Sunan al-Nasa'i - Jabir ibn 'Abdullah; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Maharab bin Dithar محارب بن دثار; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“There is no Riba except in credit.’
Grade:

Hadith #4641 - Sunan al-Nasa'i - al-Mandhar bin Malik bin Qata' المنذر بن مالك بن قطعة - أبو نضرة العبدي; Jabir ibn 'Abdullah; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Sulaiman bin Tarkhan al-Taymi سليمان بن طرخان التيمي (Sunan al-Nasa'i)
“The Messenger of Allah forbade lending on the condition of a sale, selling what you do not have, and profiting on what you do not possess.
Grade:

Hadith #4692 - Sunan al-Nasa'i - Abdullah bin Abi Qatada Ibn Rab'i عبد الله بن أبي قتادة الأنصاري السلمي; Abu Qatada ibn Rab'i; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Uthman bin 'Abdullah bin Muhab عثمان بن عبد الله بن موهب التيمي الأعرج (Sunan al-Nasa'i)
“If a woman is married off by two guardians, then the first marriage is the one that counts, and if a man sells something to two men, it belongs to the first one.”
Grade:

Hadith #4992 - Sunan al-Nasa'i - al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Amir bin Sa'd ibn Abi Waqqas عامر بن سعد بن أبي وقاص; Ma'mar bin Rashid معمر بن راشد; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Muhammad bin Thwr al-Sn'any محمد بن ثور الصنعاني أبو عبد الله; Sa'd ibn Abi Waqqas (Sunan al-Nasa'i)
“I said to Fadalah bin ‘Ubaid: ‘Do you think that hanging the hand from the thief’s neck is Sunnah?’ He said: ‘Yes; a thief was brought to the Messenger of Allah and he cut off his hand and hung it from his neck.”‘ (Daif) Abu ‘Abdur-Rahman (An-Nasai) said; Al-Hajjaj bin Artah is weak, his narrations are not used as proof.
Grade:

Hadith #5041 - Sunan al-Nasa'i - Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Sulaiman bin Tarkhan al-Taymi سليمان بن طرخان التيمي (Sunan al-Nasa'i)
The Prophet said: “Whoever follows the funeral procession of a Muslim out of faith and in the hope of reward, then offers the funeral prayer for him and waits until he is placed in his grave, then he will have two Qirats, each of which is like Mount Uhud. Whoever offers the funeral prayer for him then returns, he will have one Qirat.”
Grade:

Hadith #5047 - Sunan al-Nasa'i - Habib bin Ysar al-Kndy حبيب بن يسار الكندي الكوفي; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Yusuf bin S'hyb al-Kndy يوسف بن صهيب الكندي الكوفي; Zayd bin Arqam (Sunan al-Nasa'i)
“The Prophet said: ‘The parable of the believer who recites the Qur’an is that of a citron, the taste and smell of which are good. The parable of a believer who does not read the Qur’an is that of a date, the taste of which is good but it has no smell. The parable of a hypocrite who reads the Qur’an is that of basil, the smell of which is good but its taste is bitter. And the parable of a hypocrite who does not read the Qur’an is that of a colocynth (bitter-apple), the taste of whic
Grade:

Hadith #5082 - Sunan al-Nasa'i - Abdullah bin Burayda bin al-Husayb عبد الله بن بريدة بن الحصيب الأسلمي; Kahmas bin al-Hasan al-Tamimi كهمس بن الحسن التميمي; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘Change gray hair, but do not imitate the Jews.'”
Grade:

Hadith #5088 - Sunan al-Nasa'i - Abdur Rahman bin Harmala عبد الرحمن بن حرملة بن عمرو بن سنة; ibn Mas'ud; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى (Sunan al-Nasa'i)
“I heard the Prophet say: ‘Some of the best things with which you can change gray hair are Henna and Katam.'”
Grade:

Hadith #5092 - Sunan al-Nasa'i - Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Mu'awiya ibn Abu Sufyan; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Qatada قتادة; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي (Sunan al-Nasa'i)
“My father and I came to the Prophet and he had dyed his beard with Henna.”
Grade:

Hadith #5101 - Sunan al-Nasa'i - Aban bin Sm'h أبان بن صمعة; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى (Sunan al-Nasa'i)
“The Messenger of Allah forbade giving a false impression.”
Grade:

Hadith #5121 - Sunan al-Nasa'i - Ata'a bin al-Sa'ib al-Thaqifi عطاء بن السائب الثقفي; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“We heard that the Messenger of Allah forbade filing (the teeth) and tattoos.”
Grade:

Hadith #5138 - Sunan al-Nasa'i - Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Raba'i bin Harash bin Jahsh ربعي بن حراش (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘If one of you wants to attend ‘Isha’ prayer, let her not touch perfume.'”
Grade:

Hadith #5225 - Sunan al-Nasa'i - Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ma'mar bin Rashid معمر بن راشد; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي (Sunan al-Nasa'i)
“The Prophet used to wear a ring of gold, then he discarded it, and put on a ring of silver on which was engraved (the words): ‘Muhammad Rasul Allah.’ He said: ‘No one else should engrave his ring with an inscription like this ring of mine.’ Then he put the stone toward the palm of his hand.”
Grade:

Hadith #5240 - Sunan al-Nasa'i - Aisha bint Abi Bakr; Ash'uth bin Qays; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Masrouq bin al-Ajda' مسروق بن الأجدع; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
The Prophet forbade Al-Qaza’ (shaving part of the head and leaving part).”
Grade:

Hadith #5242 - Sunan al-Nasa'i - Jabir ibn 'Abdullah; Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Uzra bin Thabit عزرة بن ثابت بن أبي زيد (Sunan al-Nasa'i)
“I never saw any long haired man in a Hullah who was more handsome than the Messenger of Allah , and he had hair that came down to his shoulders.”
Grade:

Hadith #5328 - Sunan al-Nasa'i - ibn Umar; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Maharab bin Dithar محارب بن دثار; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“The Messenger of Allah came out to us wearing two green garments.”
Grade:

Hadith #5339 - Sunan al-Nasa'i - al-Nadr bin Shumayl al-Maazni النضر بن شميل المازني أبو الحسن النحوي; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Nafie' نافع مولى ابن عمر; Sulayman ibn Yasar سليمان بن يسار مولى ميمونة بنت الحارث; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم; Umm Salamah (Sunan al-Nasa'i)
“The Messenger of Allah said: ‘Whatever of the Izar comes below the ankles is in the Fire.'”
Grade:

Hadith #5354 - Sunan al-Nasa'i - Abdur Rahman bin al-Qasim عبد الرحمن بن القاسم بن محمد بن أبي بكر; Aisha bint Abi Bakr; al-Qasim ibn Muhammad القاسم بن محمد بن أبي بكر الصديق; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“The Prophet entered (Makkah) on the Day of the Conquest wearing a black turban.”
Grade:

Hadith #5383 - Sunan al-Nasa'i - Anas ibn Malik; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Qatada قتادة; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Usaid bin Hudair bin Sammak (Sunan al-Nasa'i)
“The metallic end of the scabbard of the Messenger of Allah was of silver, the pommel of his sword was silver, and in between were rings of silver.”
Grade:

Hadith #5496 - Sunan al-Nasa'i - Abdul Malik bin 'Umayr al-Qabti عبد الملك بن عمير بن سويد القبطي; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Mus'ub bin Sa'd ibn Abi Waqqas مصعب بن سعد بن أبى وقاص الزهرى; Sa'd ibn Abi Waqqas; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
The Messenger of Allah used to say supplication in these words: “Allahumma inni a’udhu bika min ghalabatid-dain, wa ghalabatil-‘aduwwi, wa shamatatil-a’da’. (O Allah, I seek refuge with You from being overwhelmed by debt and from being overpowered by the enemy, and from the enemy rejoicing at my misfortune.)”
Grade:

Hadith #5527 - Sunan al-Nasa'i - Hilal bin Yasaf هلال بن يساف; Husayn bin 'Abdur Rahman al-Salmi حصين بن عبد الرحمن السلمي; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Sulaiman bin Tarkhan al-Taymi سليمان بن طرخان التيمي (Sunan al-Nasa'i)
The Messenger of Allah said: “Seek refuge with Allah from the torment of the Fire and the torment of the grave, from the trials of life and death, and from the evil of Al-Masihid-Dajjal.”
Grade:

Hadith #5618 - Sunan al-Nasa'i - Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
The Prophet said: “I forbid to you small amounts of whatever intoxicates in large amounts.”
Grade:

Hadith #5640 - Sunan al-Nasa'i - Aisha bint Abi Bakr; Ishaq bin Suwayd bin Hubayra إسحاق بن سويد بن هبيرة; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Mu'adhah bint 'Abdullah معاذة بنت عبد الله; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى (Sunan al-Nasa'i)
“The Messenger of Allah forbade soaking (fruits) in Ad-Dubba’ (gourds) and Al-Muzaffat.”
Grade:

Hadith #5658 - Sunan al-Nasa'i - Abdullah/Abu Bakr bin Hafs bin 'Umar عبد الله بن حفص بن عمر - أبو بكر; Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan al-Nasa'i)
“(Fruit) would be soaked for the Messenger of Allah forbade Ad-Dubba’ (gourds), An-Naqir, and Al-Muzaffat.”
Grade:

Hadith #5700 - Sunan al-Nasa'i - ibn Umar; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Mqatl bin Hyan al-Nbty مقاتل بن حيان النبطي; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب (Sunan al-Nasa'i)
“Nabidh made from Al-Busr is forbidden and is not permissible.”
Grade:

Hadith #5715 - Sunan al-Nasa'i - Ibrahim al-Nakha'i إبراهيم النخعي; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Suwayd bin Ghaflah bin Awsajah سويد بن غفلة بن عوسجة (Sunan al-Nasa'i)
‘Umar bin Al-Khattab, may Allah be pleased with him, said: “If you fear that Nabidh may be too strong, then weaken it with water.” ‘Abdullah (one of the narrators) said: “Before it gets strong.”
Grade:

Hadith #133 - Jami' al-Tirmidhi - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري; Abdullah bin Sa'd; Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; al-Ala' bin al-Harith bin 'Abdul Warith العلاء بن الحارث بن عبد الوارث; Mu'awiya bin Salah bin Hadayr معاوية بن صالح بن حدير; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى (Jami' al-Tirmidhi)
I asked the Prophet about eating with a menstruating woman. He said: “Eat with her.”
Grade:

Hadith #600 - Jami' al-Tirmidhi - Abdullah bin Shaqayq al-Aqayli عبد الله بن شقيق العقيلي; Aisha bint Abi Bakr; Ash'ath bin Abi al-Ash'atha أشعث بن أبي الشعثاء; Ibn Sirin محمد بن سيرين الأنصاري; Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى (Jami' al-Tirmidhi)
“The Messenger of Allah would not pray in women’s covers.”
Grade:

Hadith #923 - Jami' al-Tirmidhi - Aisha bint Abi Bakr; Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري; Hisham bin 'Urwa هشام بن عروة; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Urwa ibn al-Zubayr عروة بن الزبير; Yazid bin Zari' يزيد بن زريع (Jami' al-Tirmidhi)
“At-Tahsib is nothing, it is only a place that the Messenger of Allah camped at.”
Grade:

Hadith #929 - Jami' al-Tirmidhi - Abdullah bin Ata'a عبد الله بن عطاء الطائفي; Abdullah bin Burayda bin al-Husayb عبد الله بن بريدة بن الحصيب الأسلمي; Abdur-Razzaq عبد الرزاق بن همام; Ali bin Hujr bin Iyas bin Maqatil علي بن حجر بن إياس بن مقاتل; Ali bin Ms'hr علي بن مسهر; Burayda bin al-Husayb; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Jami' al-Tirmidhi)
“A woman from Khath’am said: ‘O Messenger of Allah! My father has lived until Allah has made Hajj obligatory, and he is an elderly man who is not able to sit on the back of a camel.’ So he (pbuh) said: ‘Perform Hajj for him.'”
Grade:

Hadith #1459 - Jami' al-Tirmidhi - Abdur-Razzaq عبد الرزاق بن همام; ibn Abbas; Ikrama عكرمة; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Smak bin Hrb bin Aws سماك بن حرب بن أوس; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Jami' al-Tirmidhi)
From his father: “A women went out during the time of the Prophet (ﷺ) to go to Salat, but she was caught by a man and he had relations with her, so she screamed and he left. Then a man came across her and she said: ‘That man has done this and that to me’, then she came across a group of Emigrants (Muhajirin) and she said: ‘That man did this and that to me.’ They went to get the man she thought had relations with her, and they brought him to her. She said: ‘Yes, that’s him.’ So
Grade:

Hadith #1518 - Jami' al-Tirmidhi - Husayn bin 'Abdur Rahman al-Salmi حصين بن عبد الرحمن السلمي; Imran bin 'Uyaynah عمران بن عيينة; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Salm bin Abi al-Ja'd سالم بن أبي الجعد (Jami' al-Tirmidhi)
That the Messenger of Allah (ﷺ) said: “For a boy, there is an ‘Aqiqah. So spill blood for him and remove the harm from him.”
Grade:

Hadith #2003 - Jami' al-Tirmidhi - Da'ud bin Shabwr داود بن شابور; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Mujahid bin Jabir مجاهد بن جبر; Sufyan bin 'Uyaynah سفيان بن عيينة (Jami' al-Tirmidhi)
“They (meaning the people in general) told me that I was proud, while I rode a donkey, wore a cloak, and I milked the sheep. And the Messenger of Allah said to me: “Whoever does these, then there is no pride (arrogance) in him.'”
Grade:

Hadith #2329 - Jami' al-Tirmidhi - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Yazid bin Zari' يزيد بن زريع (Jami' al-Tirmidhi)
“O Messenger of Allah! Which of the people is the best?” He said: “He whose life is long and his deeds are good.” He said: “Then which of the people is the worst?” He said: “He whose life is long and his deeds are bad.”
Grade:

Hadith #3160 - Jami' al-Tirmidhi - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Anas ibn Malik; Hammad bin Salama حماد بن سلمة; Muhammad bin 'Abdul A'la محمد بن عبد الأعلى; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Jami' al-Tirmidhi)
from As-Suffi from Murrah: “‘Abdullah said: ‘There is not one of you but will pass over it (19:71) – They pass over it, then they avert it based upon their deeds.'”
Grade: